Design of an Efficient and Provable Secure Key Exchange Protocol for HTTP Cookies - Akram, Waseem; Mahmood, Khalid; ul Haq, Hafiz Burhan; Asif, Muhammad; Chaudhry, Shehzad Ashraf; Shon, Taeshik (Computers, Materials and Continua, 2024)
Cookies are considered a fundamental means of web application services for authenticating various Hypertext Transfer Protocol (HTTP) requests and maintains the states of clients’ information over the Internet. HTTP cookies are exploited to carry client patterns observed by a website. These client patterns facilitate the particular client’s future visit to the corresponding website. However, security and privacy are the primary concerns owing to the value of information over public channels and the storage of client information on the browser. Several protocols have been introduced that maintain HTTP cookies, but many of those fail to achieve the required security, or require a lot of resource overheads. In this article, we have introduced a lightweight Elliptic Curve Cryptographic (ECC) based protocol for authenticating client and server transactions to maintain the privacy and security of HTTP cookies. Our proposed protocol uses a secret key embedded within a cookie. The proposed protocol is more efficient and lightweight than related protocols because of its reduced computation, storage, and communication costs. Moreover, the analysis presented in this paper confirms that proposed protocol resists various known attacks.
Keywords: Authentication protocols; Cookie; CryptoGraphics; Elliptic curve; Elliptic curve cryptographic; Impersonation attack; Key exchange protocols; Provable secure; Secure key exchanges; WEB application; authentication protocol; Cookies; ECC; impersonation attack